Dr. Michele Shermak — Deep Plane Facelift — Baltimore - Shermak, Michele (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Michele Shermak, practicing in Baltimore, USA. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003280; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; usa; baltimore